A retrospective study of HBV reactivity among blood donors in Bojonegoro - Fatia Rizki Nuraini; Nina Difla Muflikhah (Universitas Ahmad Dahlan, 2026)
Hepatitis B virus (HBV) remains one of the most significant transfusion-transmitted infections (TTIs), posing ongoing challenges to blood safety in Indonesia. Regular monitoring of HBV reactivity among blood donors is crucial for evaluating the effectiveness of screening and guiding public health interventions. This study aimed to assess the prevalence and temporal trends of HBV reactivity among blood donors in Bojonegoro, while evaluating the effectiveness of current screening procedures and supporting public health interventions. A retrospective cross-sectional study was conducted on 51,351 blood donors at UDD PMI Bojonegoro between January 2020 and December 2021. Blood samples were screened using the Enzyme-Linked Immunosorbent Assay (ELISA) to detect HBV infection. Data were analyzed using descriptive statistics and cross-tabulation. A total of 261 donors tested reactive for hepatitis B, comprising 129 cases in 2020 and 132 in 2021. Although the absolute number of reactive cases increased slightly, the reactivity rate declined from 0.61% to 0.44%, coinciding with an overall increase in the number of donors. Monthly analysis revealed fluctuating patterns, with peaks observed in December 2020 and June 2021. The declining proportion of HBV reactivity suggests improvements in donor selection and public awareness. However, the continued presence of reactive cases highlights the need to strengthen screening systems, expand vaccination coverage, and adopt more sensitive detection technologies, such as Nucleic Acid Testing (NAT). Ongoing regional surveillance remains crucial to support national efforts in controlling HBV and ensuring the safety of blood transfusion services in Indonesia.